2004
DOI: 10.1007/bf02708496
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behaviour of strontium tartrate single crystals

Abstract: Strontium tartrate trihydrate (STT) crystals have been grown in silica hydrogel. Various polarization mechanisms such as atomic polarization of lattice, orientational polarization of dipoles and space charge polarization in the grown crystals have been understood using results of the measurements of dielectric constant (ε ε′ ′) and dielectric loss (tan δ δ) as functions of frequency and temperature. Ion core type polarization is seen in the temperature range 75-180°C, and above 180°C, there is interfacial pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 19 publications
8
31
0
Order By: Relevance
“…As the frequency increases, a point is reached where the space charge can not sustain and comply with the external field, and hence the polarization decreases and exhibits the reduction in the values of dielectric constant as frequency increases. This has been discussed in detail elsewhere [37][38][39]. From the data of the variation of dielectric loss (D = tan δ) with frequency of applied field at room temperature, it was observed that dielectric loss increased up to 2 kHz and followed by decreasing nature with higher frequency.…”
Section: Resultsmentioning
confidence: 92%
“…As the frequency increases, a point is reached where the space charge can not sustain and comply with the external field, and hence the polarization decreases and exhibits the reduction in the values of dielectric constant as frequency increases. This has been discussed in detail elsewhere [37][38][39]. From the data of the variation of dielectric loss (D = tan δ) with frequency of applied field at room temperature, it was observed that dielectric loss increased up to 2 kHz and followed by decreasing nature with higher frequency.…”
Section: Resultsmentioning
confidence: 92%
“…As the frequency increases, a point is reached where the space charge cannot sustain and comply the external field. Therefore the polarization decreases and exhibiting the reduction in the values of dielectric constant as the frequency increases [15]. Also, as the Mn 2+ doping level increases the value of κ increases, which suggests that the interstitial nature of the doping increases the space charge polarizability without altering the basic ferroelctric nature of the crystals.…”
Section: +mentioning
confidence: 93%
“…In the present study , growth of strontium tartrate which is different not only in respect of number of water molecules from the one grown by Arora et al but also different in terms of cell parameters, morphological development, thermal stability and FTIR spectroscopic results. As a result, the properties of the grown crystals such as mechanical properties, dielectric properties, magnetic properties are expected to be quite different from the crystals reportedly grown by other workers [14,15]. The authors have carried out indentation induced hardness testing studies on five different habit faces of the crystal, and the results thus obtained will be published elsewhere…”
Section: Introductionmentioning
confidence: 94%